Gram-Scale Quaternarization of the Anomeric Position of Carbohydrates: Dramatic Effects of Molecular Sieves on Rhodium(II)-Mediated Decomposition of Diazo Sugars - Boultadakis-Arapinis, Mélissa; Lescot, Camille; Micouin, Laurent; Lecourt, Thomas (Synthesis, 2012)
The optimization of rhodium(II) carbene mediated quaternarization of the anomeric position of carbohydrates is reported. Preparation of ketopyranosides in good and reliable yields requires reverse addition of the substrate to a highly diluted suspension of the catalyst in refluxing 1,2-dichloroethane, as well as addition of a carefully controlled amount of molecular sieves, and vigorous stirring. Following these optimized reaction conditions, functionalization of the anomeric position of carbohydrates can finally be performed on a preparative scale.
Keywords: rhodium; carbenes; molecular sieves; insertion; carbohydrates